2023
DOI: 10.3390/v15061374
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Presence and Reversibility of Subclinical Arterial Damage in HCV-Infected Individuals and Matched Controls

Abstract: Background: The arterial pathology and mechanisms of increased cardiovascular disease (CVD) risk in HCV-infected individuals are not yet clear. The aim of this study was to identify types of arterial pathology in treatment-naive chronic HCV patients and to test their reversibility after successful treatment. Methods: Consecutive, never-treated, HCV-infected patients were compared with age and CVD-related risk factors, matched controls, healthy individuals (HI), patients with rheumatoid arthritis (RA) and peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…HCV-related neuropathies include symmetrical axonal sensorimotor neuropathy, accounting for over 50% of cases; distal symmetric painful small-fiber neuropathy, with predominantly sensory features; mononeuritis multiplex; pure motor polyneuropathy; or, rarely, demyelinating and autonomic neuropathies, leading to a reduced quality of life [ 10 , 40 , 41 ]. The introduction of an all-oral DAA treatment for HCV has led to impressive results regarding viral eradication; however, the impact on HCV-related EHM is still in doubt, even though most studies have revealed an ameliorating effect [ 42 , 43 , 44 , 45 ]. We conducted a prospective, single-center study to estimate the prevalence and impact of HCV eradication in HCV-associated neuropathy in the absence of MCG.…”
Section: Discussionmentioning
confidence: 99%
“…HCV-related neuropathies include symmetrical axonal sensorimotor neuropathy, accounting for over 50% of cases; distal symmetric painful small-fiber neuropathy, with predominantly sensory features; mononeuritis multiplex; pure motor polyneuropathy; or, rarely, demyelinating and autonomic neuropathies, leading to a reduced quality of life [ 10 , 40 , 41 ]. The introduction of an all-oral DAA treatment for HCV has led to impressive results regarding viral eradication; however, the impact on HCV-related EHM is still in doubt, even though most studies have revealed an ameliorating effect [ 42 , 43 , 44 , 45 ]. We conducted a prospective, single-center study to estimate the prevalence and impact of HCV eradication in HCV-associated neuropathy in the absence of MCG.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoglobulinemic vasculitis is a systemic disorder, determined by the deposition of cryoglobulins within vessel walls associated with increased mortality and high healthcare costs in patients with chronic hepatitis C (CHC) [9], and HCV eradication is not always followed by a resolution of the damage caused by MC. Indeed, as documented for other extrahepatic manifestations of CHC, such as lymphoproliferative disorders [10,11], renal and ocular involvement, and cardiovascular and cerebrovascular disorders [10,12], after clearance of HCV via antiviral therapy, in particular with Direct-Acting Antiviral (DAA) therapies, disappearance of cryoglobulinemia is observed in only about 50% of cases [10], which highlights how the aforementioned therapy does not have consistent effects on the presence of MC. A correlation between HCV infection and cholestasis has already been established [13,14]; indeed, the onset of cholestasis in CHC is thought to be determined by direct viral cytotoxicity of hepatocytes and is associated with a weak HCV-specific T-cell response, which is predominantly carried out by Th2 cells, leading to increasingly higher levels of viral replication and amplification of the intrahepatic damage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides MCV and B-cell NHL, chronic HCV infection causes a spectrum of extrahepatic manifestations that include diabetes and cardiovascular disease, which is an important cause of mortality in infected people. Although HCV-associated B-cell lymphoproliferative disorders and cardiovascular disease are driven by different mechanisms, inflammation vs antigenic pressure and gene mutation, they share the characteristic of regressing after antiviral therapy as especially illustrated by the recent use of highly effective direct-acting antivirals ( 4 , 6 8 ). While in the case of HCV-associated cardiovascular disease no risk factor have been identified except for those canonical such as diabetes, smoking and hypertension ( 9 ), the fact that only a minority of CHC patients develop HCV pos MCV suggests specific risk factor(s) that, however, remain elusive.…”
Section: Introductionmentioning
confidence: 99%